New approaches in harnessing wave energy: with special attention to small islands - Fadaeenejad, Mohsen; Shamsipour, R.; Deilami, Soheil Rokni; Gomes, Chandima (Elsevier, 2014)
The application of renewable energies has increased rapidly in the previous decade to solve some problems such as growing energy demand and environmental issues. Wave power as a high potential renewable energy, is more predictable compared to other renewable sources. Although there are many research works about wave energy, however a few of them considered a suitable wave energy converter (WEC) as a power system for remote islands. Wave energy potential for remote islands is discussed in this review by regarding environmental impacts, various types of wave energy converters and applied wave power projects for various islands. The results show that wave energy plays a key role for sustainable development of offshore islands by considering the traditional looks and environmental protection.